Morphea and Hormonal Therapy: A Possible Association - Liliana Saraiva; Gisela Eugénio; Cátia Duarte (Sociedade Portuguesa de Dermatologia e Venereologia, 2020)
Morphea is a rare inflammatory disorder with an unknown etiology. We report the case of a 35-years-old woman presenting with an 18-month history of skin thickening on the extremities and trunk, and inflammatory arthralgia. Complaints started 2-weeks after a fertility treatment. The physical exam and workup confirmed the diagnosis of morphea, and the patient started treatment with deflazacort and methotrexate, with significant improvement. Six years later, the patient was submitted to another fertility treatment with exacerbation of the disease. The temporal association between the fertility treatments and the onset and further worsening of morphea suggest an influence of sex hormones on its pathophysiology.